2021
DOI: 10.1111/jonm.13421
|View full text |Cite
|
Sign up to set email alerts
|

Leadership, professional quality of life and moral distress during COVID‐19: A mixed‐methods approach

Abstract: Aim To understand the impact of professional stressors on nurses' and other health care providers' professional quality of life and moral distress as they cared for patients during the COVID‐19 pandemic. Background Health care providers caring for patients during the COVID‐19 pandemic are at increased risk of decreased professional quality of life and increased moral distress. Methods A convergent mixed‐methods design and snowball sampling wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 40 publications
5
44
0
4
Order By: Relevance
“…Respondents described that their managers did not have enough knowledge of how to lead in a crisis and considered whether managers had too limited a degree of knowledge or they were too inexperienced to handle the situation. This is consistent with earlier studies showing that managers need to have better training in disaster management, and that managers need more organisational support to minimize their own challenges during and beyond the pandemic (Ness et al, 2021 ). It is therefore essential that there is a clear approach to crisis management, and that lessons and experiences are used for future pandemic situations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Respondents described that their managers did not have enough knowledge of how to lead in a crisis and considered whether managers had too limited a degree of knowledge or they were too inexperienced to handle the situation. This is consistent with earlier studies showing that managers need to have better training in disaster management, and that managers need more organisational support to minimize their own challenges during and beyond the pandemic (Ness et al, 2021 ). It is therefore essential that there is a clear approach to crisis management, and that lessons and experiences are used for future pandemic situations.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, it is of utmost importance that staff are encouraged to express their feelings and sources of distress and to openly discuss their experiences and challenges in their care of COVID‐19 patients (Bianchi et al, 2021 ; Labrague, 2021 ). Consequently, when managers prioritize staff's well‐being, their trust in management will increase (Jackson & Nowell, 2021 ; Ness et al, 2021 ; Vázquez‐Calatayud et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moral distress has been a prominent theme for healthcare workers during the pandemic. [134][135][136][137] In a study in the Netherlands, two sources of moral distress that increased in COVID-19 (scarcity of resources and the perception of colleagues acting unsafely) were significant predictors of burnout. 103 In a Toronto hospital, moral distress was strongly related to emotional exhaustion and accounted for most of the difference in burnout between roles (nurses vs. other health professionals vs. other staff with regular patient contact; Hunter J, personal communication).…”
Section: Moral Distressmentioning
confidence: 99%
“… 41 This study is about staff, but, nota bene, the very presence of first-line managers in care is crucial for giving emotional support to coworkers and to ensure the concern of patients and families as a relational inclusion, that is, ethics of care. Ness et al , 42 for instance, showed that lack of support during COVID-19 increased moral distress. The frustration caused by the pandemic might risk the exacerbating of an already unhelpful narrowing of identification of belonging, in order to emotionally endure these stressing circumstances.…”
Section: Discussionmentioning
confidence: 99%